Pengaruh Independensi, Profesionalisme dan Pengalaman Kerja Auditor Terhadap Kualitas Audit Dengan Kepuasan Kerja Sebagai Variabel Intervening Pada PT. Permodalan Nasional Madani - Iriawan , Bayu; Subaidja , Steph (CV. Era Digital Nusantara, 2025)
This study aims to examine the influence of auditor independence, professionalism, and work experience on audit quality with job satisfaction as an intervening variable at PT Permodalan Nasional Madani. The research employs an explanatory quantitative method with a sample of 68 internal auditors selected through purposive sampling. Data were collected using questionnaires and analyzed using Structural Equation Modeling (SEM) based on Partial Least Square (PLS). The research results demonstrate: (1) auditor independence has a significant positive effect on audit quality with a path coefficient of 0.493; (2) auditor professionalism has a significant positive effect on audit quality with a path coefficient of 0.288; (3) auditor work experience has a significant positive effect on audit quality with a path coefficient of 0.301; (4) job satisfaction has a significant positive effect on audit quality with a path coefficient of 0.213; and (5) job satisfaction is proven to significantly mediate the relationship between auditor independence, professionalism, and work experience with audit quality. This study provides theoretical contributions to understanding the factors influencing audit quality and offers practical implications for management in improving internal auditor performance.